2015
DOI: 10.2514/1.g000837
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary Pilot Action Through Biodynamics for Helicopter Flight Dynamics Simulation

Abstract: This work presents the integration of detailed models of a pilot controlling a helicopter along the heave axis through the collective control inceptor. The action on the control inceptor is produced through a biomechanical model of the pilot's limbs, by commanding the activation of the related muscle bundles. Such activation, in turn, is determined by defining the muscle elongations required to move the control inceptor in partial derivative of (♠) with respect to (♣)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…they are actuated by multiple agonist/antagonist pairs: therefore, the resulting model would be underdetermined because of overactuation, and special techniques would have to be applied to be estimate the equivalent impedance at each joint. While similar experiences have been successfully carried out by the authors, regarding in particular the upper limbs' impedance at the control inceptors [11,25], it was concluded that for this particular case the more simplified approach relying on generic linear viscoelastic elements is sufficient for comfort related analysis.…”
Section: Multibody Dynamics Modelmentioning
confidence: 84%
“…they are actuated by multiple agonist/antagonist pairs: therefore, the resulting model would be underdetermined because of overactuation, and special techniques would have to be applied to be estimate the equivalent impedance at each joint. While similar experiences have been successfully carried out by the authors, regarding in particular the upper limbs' impedance at the control inceptors [11,25], it was concluded that for this particular case the more simplified approach relying on generic linear viscoelastic elements is sufficient for comfort related analysis.…”
Section: Multibody Dynamics Modelmentioning
confidence: 84%
“…It would, however, also make the model underdetermined due to overactuation, and special techniques would have to be applied to estimate the equivalent impedance at each joint. While similar experiences have been successfully carried out by the authors, regarding, in particular, the upper limbs' impedance at the control inceptors [28,29], it was concluded that for this particular case the simpler approach relying on lumped viscoelastic elements is sufficient for the targeted analyses.…”
Section: Torso Modelmentioning
confidence: 87%
“…The upper limb muscles activations estimated in the inverse dynamics step, and the subsequent optimisation problem, are augmented during the direct dynamics phase with a contribution proportional the muscles' length variation and elongation velocity, with respect to the reference values estimated during the inverse kinematics step. For the single muscle this contribution, which models the reflexive part of the muscular activation behaviour [28,45], is (17) where ref is the reference muscle length in the pose estimated in the inverse kinematics step and k p ,k d are proportional and derivative gains. The total activation of each muscle bundle in the upper limb therefore is…”
Section: Direct Dynamicsmentioning
confidence: 99%
“…This way, the effects of this kind of motion on human health, comfort, and performance can be predicted [138]. Human control actions can be divided into two general categories: voluntary and involuntary [139]. The models studied in the previous sections all belonged to the first category.…”
Section: Biodynamic Modelsmentioning
confidence: 99%